Evaluating the Urban Public Transportation Network in Lattakia City Using GIS Techniques - Shaza Assaad; Yara Salloum (Tishreen University, 2020)
The city of Lattakia suffers from a large increase in travel demand, which made the movement in the city a great deal of suffering, with all this congestion and delays. This research presents an evaluation of the quality of public transport in Lattakia city based on available information about the transport network using GIS techniques, and reaching an accurate assessment of the network coverage and the degree of network connectivity, to increase the efficiency or public transport performance. This study was conducted in Lattakia city and the entire public transport network in the city was studied in order to facilitate mobility in the city, and to reduce congestion and delays as much as possible. This study has found significant results in this field, and has presented a clear description of the reality of public transport network in the city, where it was found that the performance of public transport is generally weak and developed a range of solutions that will have appositive impact when applied, which will alleviate the suffering of the public transport and will raise the level of performance and limit the waste of time and congestion. تعاني مدينة اللاذقية من زيادة كبيرة للطلب على النقل, وذلك نتيجة تضخم عدد القاطنين والوافدين إلى المحافظة وزيادة عدد السيارات الخاصة والعامة التي زادت الازدحام المروري, الأمر الذي جعل من التنقل ضمن المدينة معاناة كبيرة مع كل هذا الازدحام وأزمنة التأخير. يقدم هذا البحث تقييماً لجودة النقل العام ضمن مدينة اللاذقية, وذلك بالاعتماد على المعلومات المتاحة حول شبكة النقل في النطاق العمراني لمدينة اللاذقية, بالاستفادة من تقنيات نظم المعلومات الجغرافية, والوصول إلى تقييم دقيق لدرجة تغطية شبكة النقل الداخلي للمدينة, ودرجة ترابط الشبكة, ومدى جودة خدماتها, واتخاذ إجراءات لزيادة فعالية أداء النقل الداخلي, وقد أجريت الدراسة ضمن مدينة اللاذقية وتمت دراسة كامل خطوط شبكة النقل الداخلي ضمن المدينة, وذلك سعياً لتيسير حركة المرور والنقل, والعمل على التقليل من الازدحام وأزمنة التأخير قدر الإمكان. لقد توصلت الدراسة إلى نتائج هامة في هذا المجال, وقدمت وصفاً واضحاً لواقع النقل العام في المدينة, حيث وجد أن أداء النقل العام ضمن مدينة اللاذقية يعد ضعيفاً بشكل عام, ووضعت مجموعة من الحلول التي سيكون لها أثر إيجابي عند تطبيقها, مما سيخفف من معاناة المتنقلين, وسيرفع من مستوى أداء شبكة النقل الداخلي ويحد من الازدحام وهدر الوقت.